Los Peces terciarios de las cuencas continentales ibéricas: Marco histórico y registro fosil conocido - Peña Zarzuelo, A. De la (Coloquios de Paleontología, 1995)
Sixty-fivc tossil beds are studicd from fonricen Tcrtiary continental hasins from the Iberia Peninsula. Eighteen spccies from six families and orders are presented: Probably (2) Esocae indeí., Cyprinidae (Cypriniformes), Characidae (Characiformes), Bagridae (Siluriformes), Cyprinodontidae (Cyprinodontiformes), (iobiidae (Cobiformes) and basal pereiform from family indet. and Ceníropomidie (Perciformes). Recent represenlatives frorn Tcrtiary fish record inelude species from Barbus. Rutilus Leuciscus , (Cyprinidae), and Aphanius (Cyprinodontidac). Palabras claves: Teleósteos ([2] Esoeae, Cipriniformes, Siluriformes, Characiformes, (iobiiformcs, Perciformes). Terciario, cuencas continentales